Character Education as a Preventive Strategy Against School Bullying: A Qualitative Study in an Islamic Senior High School - M. Rizal Rizqi; Khotimatus Sholihah; Nur Azizah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
School bullying remains a persistent challenge in educational settings, indicating that character education has not yet been optimally internalized into students' everyday behavior. Although numerous schools have implemented character education programs, limited research has explained how character education functions as a preventive mechanism against bullying, particularly in Islamic senior high schools. This study aims to analyze the implementation of character education as a preventive strategy against school bullying at MA Rohmatul Ummah Karanganom. A qualitative case study approach was employed using participant observation, semi-structured interviews, and documentation. Data were analyzed through the interactive model of Miles, Huberman, and Saldaña, involving data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings reveal that character education is implemented through an integrated school-wide approach encompassing classroom learning, religious habituation, teacher role modeling, extracurricular activities, and school culture. These programs function as preventive mechanisms by fostering empathy, mutual respect, self-discipline, responsibility, and prosocial behavior through continuous moral reinforcement and positive social interaction. The implementation of character education contributes to reducing bullying tendencies, strengthening peer relationships, and creating a positive school climate that encourages peaceful conflict resolution. The novelty of this study lies in proposing an empirical model that explains how integrated character education operates as a preventive strategy against bullying by linking school culture, religious values, teacher role modeling, and students' social interactions within an Islamic educational context.